Factors that affect the implementation of the Integrated Development Plan (IDP) : the case of Molemole Local Municipality in Limpopo, South Africa - Mabuza, Constance Annah (University of Limpopo, 2016)
Integrated Development Plan (IDP) are required for municipalities to function effectively. Local municipalities in South Africa use IDPs as a method to plan for the present and future development in their respective areas.The primary objectives of this study was to assess factors that facilitate or hinder successful implementation of the prioritised programmes or projects in the Integrated Development Plan of the Molemole Local Municipality. The study used qualitative approach to collect data from municipal officials, municipal council and community representatives. The study revealed that the community were not aware of the programmes or projects identified in the IDP and that there is lack of capacity to effectively implement the IDP and, communication between municipal employees and the community is not perceived to be adequate.The study recommends that the municipality should conduct training, improve communication methods and conduct awareness on IDP processes.
Thesis (MBA.) -- University of Limpopo, 2016
Keywords: Municipality; IDP; Communication; Integrated rural development; Rural development; Local government -- South Africa -- Limpopo